Epidemiological Characteristics of Rodents and Chiggers with Orientia Tsutsugamushi in the Republic of Korea - Park, Jung Wook (Korean J Parasitol, 2020)
A survey of rodents and chiggers associated with Orientia tsutsugamushi was conducted in a rural region of the Republic of Korea (Korea) between 2014 and 2018. Overall Apodemus agrarius 15.2% had the highest seropisitive for O. tsutsugamushi, followed by Myodes regulus 11.4%. Monthly risk factors using logistic regression analysis were not associated with O. tsutsugamushi infections in rodents. The overall prevalence rate of O. tsutsugamushi among chiggers was 0.3%. The chigger (Leptotrombidium scutellare) and monthly (October) risk factors were associated with O. tsutsugamushi human infections (P<0.05). Orientia tsutsugamushi infections are endemic in rodents in Korea and people, for example, soldiers who are active outdoors, must employ preventive measures, especially during October (P<0.05). When there are many reports of O. tsutsugamushi infections in Korea. The Boryong strain 85.7% (2/14) was the most common strain detected in chiggers, followed by the Shimokoshi 7.1% (1/14) and Karp 7.1% strains.